ANALYSIS OF THE SAFETY CONDITION OF HUMANS, THE ENVIRONMENT AND WORKING CONDITIONS DURING THE FERTILIZERS HANDLING: Array - Mykhailova, E.; Protasenko, O.; Moroz, M.; Reznichenko, A. (Municipal economy of cities. Series: «Economy science», 2021)
The article considers the problem of efficiency and safety of fertilizers using in agriculture. Fertilizers are an integral part of the food fund formation system, which determines food safety at the national and world levels. Thus, the research of the safety state of fertilizers handling is an actual practical task in the context of sustainable development of society. The aim is an analysis of the efficiency of fertilizer using in agriculture, determining the level of fertilizer safety for the environment, human health and working conditions. Organic and mineral fertilizers are the most widespread in agriculture. Fertilizers are one of the main factors in improving the quantity and quality of agricultural products. The rational usage of fertilizers helps to maintain the nutrients and humus balance in the soil, to improve its fertility. The organic fertilizers include organic compounds of animal, vegetable, industrial and household origin. They have different decomposition degrees and create different nutrients complexes (nitrogen, phosphorus, potassium and others), which are well absorbed by plants. The danger of organic fertilizer usage is associated with the possible presence of bacteria, viruses, parasites, antibiotics, steroid hormones, pesticides in their composition. The release of these agents into the environment disturbs the ecological balance of the soil and degrades its quality, pollutes water, contributes to food epidemics, causes chronic diseases and acute poisoning in humans. Mineral fertilizers are artificially synthesized chemical compounds that are needed to maintain the inorganic compounds balance in the soil. Irrational usage of mineral fertilizers leads to changes in soil composition and properties, disruption of nutrients natural cycles, pollution of the environment and agricultural products by nitrates, heavy metals, halogens and radionuclides. All this negatively affects the quality of human life and health. In addition, improper fertilizer handling during production, storage, transportation and usage worsens the working conditions, leads to occupational diseases, increases explosion and fire levels. It is necessary to optimize forms, rates, timing and methods of fertilizers application, adhere to treatments frequency and distance from settlements, adhere to labour protection norms, rules and instructions and apply collective and individual protection means during fertilizers working.